Contribution of Human Herpesvirus 8 and Herpes Simplex Type 2 to Progression of Carotid Intima-Media Thickness in People Living With HIV. (29th January 2019) - Lidón, Fernando; Padilla, Sergio; García, Jose A; Fernández, Marta; García, Javier; Ortiz de la Tabla, Victoria; Gutiérrez, Félix; Masiá, Mar
Abstract: Background: Human herpesvirus 8 (HHV-8) is a lymphotropic and vasculotropic herpesvirus with potential pro-atherogenic effects. We explored the influence of coinfection with HHV-8 and other herpesviruses on the rate of progression of carotid intima-media thickness (cIMT) in virologically suppressed people living with HIV (PLWH). Methods: Prospective cohort study including men who have sex with men (MSM) infected with HIV. At the baseline visit, IgG antibodies against HHV-8 and other herpesviruses, highly sensitive C-reactive protein (hsCRP) levels, and Framingham risk scores were measured. To evaluate the progression of cIMT, successive measurements with high-resolution carotid artery ultrasound were performed over an 8-year period. Adjusted general linear mixed models were used to assess factors associated with faster cIMT progression. Results: One hundred forty-one participants with suppressed HIV-RNA (<200 copies/mL) at cIMT measurement during the study period were included. Forty-six (31.3%) were coinfected with HHV-8 and 76 (54%) with herpes simplex virus 2 (HSV-2). Factors associated with faster cIMT progression adjusting for CD4 cell counts, time between cIMT measurements, hepatitis C, varicella zoster virus, and cytomegalovirus coinfection were seropositivity for HHV-8 ( P = .059), HSV-2+HHV-8 coinfection ( P = .027), Framingham risk score ( P = .057), and hsCRP ( P = .027). Coinfection with HHV-8 was independently associated with higher levels of hsCRP (odds ratio, 1.09; 95% confidence interval, 1.02 to 1.17; P = .016). When hsCRP and HHV-8 were simultaneously included in the adjusted model, the relationship of HHV-8 with cIMT progression was attenuated. Conclusions: HHV-8 might contribute to progression of cIMT with a more prominent role when it coinfects with HHV-2 in virologically suppressed PLWH, and this effect could be driven by systemic inflammation.